Novel learning accelerates systems consolidation of a contextual fear memory. Issue 7 (11th March 2016) - Haubrich, Josue; Cassini, Lindsey Freitas; Diehl, Felipe; Santana, Fabiana; Fürstenau de Oliveira, Lucas; de Oliveira Alvares, Lucas; Quillfeldt, Jorge Alberto
ABSTRACT: After initial encoding memories may undergo a time‐dependent reorganization, becoming progressively independent from the hippocampus (HPC) and dependent on cortical regions such as the anterior cingulate cortex (ACC). Although the mechanisms underlying systems consolidation are somewhat known, the factors determining its temporal dynamics are still poorly understood. Here, we studied the influence of novel learning occurring between training and test sessions on the time‐course of HPC‐ and ACC‐dependency of contextual fear conditioning (CFC) memory expression. We found that muscimol was disruptive when infused into the HPC up to 35 days after training, while the ACC is vulnerable only after 45 days. However, when animals were subjected to a series of additional, distinct tasks to be learned within the first 3 weeks, muscimol became effective sooner. Muscimol had no effect in the HPC at 20 days after training, exactly when the ACC becomes responsive to this treatment. Thus, our data indicates that the encoding of new information generates a tight interplay between distinct memories, accelerating the reorganization of previously stored long term memories between the hippocampal and cortical areas. © 2016 Wiley Periodicals, Inc.